Epidemiological and quality of life analysis of patients with ANOCA (Research, Society and Development, 2022)
Introduction: A portion of patients affected by angina has ANOCA (angina with non-obstructive coronary arteries). Objectives: To determine the epidemiological and quality of life aspects of individuals with angina without coronary obstruction. Material and methods: This is an observational cross-sectional study, conducted by applying questionnaires (SAQ-7 and SF-36) in patients undergoing catheterization in a single hospital from September 2021 to June 2022, and who did not have significant coronary artery obstructions (≥50%). Results: Patients had a mean age of 59.2 years and 60.47% of the sample was female. The main comorbidities found were dyslipidemia (81.4%); hypertension (81.4%); and anxiety (55.81%). Regarding lifestyle habits, 67.44% of patients were sedentary and 34.88% were smokers. According to SAQ-7, for physical limitation, 34.88% patients were in the poor to fair grade. The quality of life had the worst results, with 86.05% of the sample presenting poor to fair. For SF-36, limitations for physical and emotional aspects had median of zero and functional capacity of 25. Discussion: ANOCA patients presented impacts mainly on quality of life, functional capacity, physical limitations, and limitations due to emotional problems, which is in agreement with literature data. Conclusion: Despite de absence of obstructive coronary lesions, patients with ANOCA have significant comorbidities and quality of life impairment, requiring atention from their physicians.